Kerch ironstones as unconventional Nd and MREE resources: features and prospects - Anna V. Nekipelova; Elina V. Sokol; Svetlana N. Kokh; Ksenia A. Filippova (Руды и металлы)
Based on the mineralogy and major and trace element composition (including REE+Y) of bulk samples and in separate size fractions of the ore, the contribution of different REE+Y species to the total REE budget of ironstones from the Kamysh-Burun trough was estimated. Kerch ores have the structure of REE+Y accumulation typical for marine sedimentary iron ore deposits. Light REEs form independent mineralization of authigenic phosphates (rhabdophane-type LREE(PO4)∙nH2O phases) enriched in La, Pr, Nd, and Ca. Medium REEs are mainly adsorbed on Fe3+-(oxy)hydroxides forms. The coexisting Nd and MREE enrichment combined with Th and U depletion allow considering the Kerch ironstones as commercially attractive unconventional resources of rare-earth elements.